34.3k views
3 votes
-38 - 7y = 2 - 7(y + 6)

User CreyD
by
4.1k points

2 Answers

2 votes

Answer:

No solution

Explanation:

First do distribute property

-38-7y=2-7y-42

then combine like terms the 2 and the -42

-38-7y=-40-7y add 7y from both sides

-38+y=-40 add 38 to -40 you get -2

0=-2 no solution

User Mitchel Verschoof
by
4.8k points
5 votes

Answer:

No solution

Explanation:


-38 - 7y = 2 - 7(y + 6)\\\\\mathrm{Expand\:}2-7\left(y+6\right):\quad -7y-40\\-38-7y=-7y-40\\\\\mathrm{Add\:}38\mathrm{\:to\:both\:sides}\\-38-7y+38=-7y-40+38\\\\Simplify\\-7y=-7y-2\\\\\mathrm{Add\:}7y\mathrm{\:to\:both\:sides}\\-7y+7y=-7y-2+7y\\\\Simplify\\\\0=-2\\\mathrm{The\:sides\:are\:not\:equal}\\No\: solution

User Kianenigma
by
5.0k points